Association Between Single Nucleotide Polymorphism Of Calpain1 Gene And Meat Tenderness Traits In Different Genotypes Of Chicken: Malaysian Native And Commercial Broiler Line - Abtehal Y. Anaas; Mohd Nazmi Abd Manap (World Academy of Science, Engineering and Technology, 2024)
Volume:10 No:2